Experimental investigation on the ventilation performance of diffuse ceiling ventilation in heating conditions. (November 2021) - Peng, Pei; Pomianowski, Michal; Zhang, Chen; Guo, Rui; Jensen, Rasmus Lund; Jønsson, Kim Trangbæk; Gong, Guangcai
Abstract: This paper aims to investigate the performance of diffuse ceiling ventilation (DCV) in heating mode by a full-scale chamber. Eleven cases combined with different exhaust positions, supply air change rates, internal heat source intensities, and the type and location of contaminant sources were tested. The contaminant removal effectiveness (CRE) and temperature effectiveness (TE) were utilized to evaluate the ventilation effectiveness of DCV. It is found that thermal discomfort due to vertical temperature differences or draught is negligible for all tested cases. The results demonstrate that the effect of exhaust positions on CRE depends on the existence of internal heat source. With the presence of heat source, the room air can reach a good mixing, and the effect of exhaust positions is therefore limited. Nevertheless, when there is no internal heat source, the lower position can force the supply air to enter the occupied zone and improve ventilation performance. Increased air change rates can significantly improve indoor air quality, but have a little influence on ventilation effectiveness. CRE is strongly influenced by the internal heat source intensity and the contaminant source type. With the increase of heat source intensity, CRE increases notably from 0.28 to 0.82. As for different contaminant source types, CRE is about 1.3 under the active source (with heat), but only 0.68 and 0.82 under the passive source (without heat). This study is beneficial to the further design and optimization of DCV for its broader heating application. Highlights: The performance of diffuse ceiling ventilation (DCV) in heating mode was studied. Contaminant removal effectiveness (CRE) and temperature effectiveness (TE) used. Different parameters impacting the ventilation performance of DCV were discussed. Exhaust position can affect TE, but its effect on CRE depends on the heat source. Internal heat source and the type of contaminant source affect CRE significantly.